Electrostatic waves in pressure waves bounding solar wind stream interaction regions - Xianghan Wang; Jianpeng Guo (地球与行星物理论评, 2024)
The solar wind stream interaction region is bounded by a pair of forward-reverse pressure waves that commonly steepen into forward and reverse shock waves at large heliocentric distances. It remains unclear whether electrostatic (ES) wave modes are present in pressure wave ramps and provide energy dissipation as they do in shock waves. In this study, we identified 76 pressure waves bounding SIRs near 1 AU utilizing Wind measurements from 1995–2020 and determined that 27 pressure waves (18 forward and nine reverse) had at least one waveform capture in the pressure ramp. The ES wave modes included three main wave types: ion acoustic waves (IAWs), Langmuir waves, and ES solitary waves (ESWs). The dominant mode in the forward pressure wave ramp was the IAW, whereas those in the reverse pressure wave ramp were the Langmuir wave and ESW. The IAWs provided an approximately anomalous resistivity of 0.01–2 Ω·m. A positive correlation existed between the maximum of the IAW amplitude and the strength of the pressure wave. These results indicate that IAWs can potentially provide energy dissipation for forward pressure waves.